The Influence Of Purchasing Strategies On Manufacturing Performance With The Moderating Effect Of Purchasing Strategic Integration - Perumal, Thrulogachantar (2009)

(untitled)
The objective of this study is to examine the influence of Purchasing Strategies on Manufacturing Performance being moderated by the effect of Purchasing Strategic Integration.